Rancang Bangun Sistem Aplikasi Kasir Dan Inventaris Barang Menggunakan Barcode Berbasis Android Pada Toko Makmur Jaya - Achmad Fahreza Supriyanto (JURNAL VOKASI TEKNIK, 2026)
In the modern era, technological advancements influence the changing needs and desires of consumers. In the case of Toko Makmur Jaya, challenges related to transaction processes and inventory management are evident. The current manual system often causes data entry errors and slows down transaction processes, negatively impacting the store’s progress. This study aims to address these issues by designing and developing an Android-based Cashier and Inventory Management Application using barcode technology for product identification. the research employs the Waterfall methodology, which includes data collection, system design, application implementation, application testing, and maintenance. The application is developed using the Kodular.IO platform and SQLite database, and operates offline (Local Client) to avoid reliance on internet connectivity. The outcome of this research is an Android-based cashier and inventory management application integrated with a barcode scanner.